'The lecturer should know what they are talking about': Student Union Officers perceptions of teaching-related CPD and implications for their practice. Issue 2 (4th March 2017) - Turner, Rebecca; Spowart, Lucy; Winter, Jennie; Muneer, Reema; Harvey, Chloe; Kneale, Pauline
Abstract: Continuing professional development (CPD) for HE academic staff, through accredited courses for new lecturers, teaching innovation grants, peer review, mentoring and conference attendance, is firmly established practice, engagement with these activities may be essential to career progression. The input of students to CPD, student awareness of, or active engagement with these activities is limited despite the growing emphasis on agendas such as 'student engagement' and 'students as partners'. In this paper, we examine their perceptions of teaching-oriented CPD and the potential contributions of students through interview data collected from eight elected Student Union (SU) Officers. This informs a discussion of the mechanisms by which SU officers can influence teaching-related developments in HE and provide recommendations to enhance future working relationships between SU and providers of CPD.